238 A qualitative exploration of restraint decisions made by paramedics and advanced paramedics in the context of acute behavioural disturbance (ABD) in the pre-hospital setting. (1st May 2022) - Lindridge, J; Blackwood, L; Edwards, T
Abstract : Background: Acute behavioural disturbance, also known as excited delirium, is a medical emergency. Paramedics are required to balance competing concerns, including the risks of restraint to the patient, the need for diagnostic accuracy and the need for compliance with relevant legislation. Decisions take place in the context of challenging situations and paramedics are required to work closely with other professionals, such as the police. Method: 17 semi structured interviews 1 and focus group were undertaken with Paramedics and Advanced Paramedic Practitioners. This data is being analysed using reflexive thematic analysis (Braun and Clarke, 2006), informed by critical realism. Results: We have identified five tentative themes: Professional identity and patient advocacy, adequacy of clinical management strategies, managing complexity and ambiguity, inter-professional relationships and fear of professional consequences. These candidate themes will continue to be developed and refined during the remaining analysis. Conclusion: Restraint decisions take place in the context of high levels of complexity and ambiguity, limited clinical management options and rely on effective communication and collaboration with partner agencies, such as the police. Paramedics are motivated by patient-centred issues including advocacy and improving outcomes, and at times experience tensions with practitioner-centric issues such as fear of adverse professional consequences. Reference: Braun V, Clarke V. Using thematic analysis in psychology. Qualitative Research in Psychology 2006;3 (2):77–101. Conflict of interest: None to declare. Funding: None.